Laminate, packaging bag and package
The laminate with a mechanically recycled PET film and reduced cyclic trimer content addresses puncture strength and contamination issues in recycled PET films, ensuring high hygiene and resistance to cyclic oligomer entry.
Patent Information
- Application Number
- JP2023109866
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Recycled PET films face issues with decreased puncture strength due to molecular crystal orientation changes, leading to potential pinholes and contamination from cyclic oligomers entering the package.
A laminate using a mechanically recycled PET film with a cyclic trimer content of 0.80% by mass or less, combined with a sealant layer, to enhance puncture strength and reduce cyclic oligomer entry.
The laminate provides high hygiene and puncture resistance, preventing cyclic oligomers from entering the package even if pinholes occur, ensuring the contents remain uncontaminated.
Smart Images

Figure 2025008030000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a packaging bag, and a packaging body. [Background technology]
[0002] Packaging bags with laminates based on recycled polyethylene terephthalate (PET) are environmentally friendly packaging bags, and their active use is expected. Known methods for recycling PET include a mechanical recycling method in which PET is treated at high temperature and reduced pressure, and a chemical recycling method in which PET is chemically decomposed. Meanwhile, in the production process of PET, cyclic oligomers are generated as a side reaction of the polymerization reaction. The cyclic oligomers adhere to the mold during processing of PET, reducing the production efficiency, and remain in the PET, affecting the hygiene of the contents in the packaging bag. Therefore, it is necessary to reduce the cyclic oligomers in PET. Patent Document 1 discloses a highly hygienic printed resin film that contains chemically recycled polyester and has a reduced content of cyclic trimers, taking into consideration the hygiene aspects of mechanically recycled polyester. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-002890 A Summary of the Invention [Problem to be solved by the invention]
[0004] There is a concern that the puncture strength of recycled PET films produced through a recycling process may decrease due to changes in the orientation of molecular crystals. Therefore, pinholes may occur in packages using recycled PET films due to rubbing or being pierced by sharp objects during transportation. There is a concern that low molecules such as cyclic oligomers contained in the PET film may penetrate into the inside of the package through such pinholes. Therefore, the present disclosure provides a laminate that uses mechanically recycled PET film and has sufficiently high hygiene, as well as a packaging bag and a package including such a laminate. [Means for solving the problem]
[0005] One aspect of the present disclosure provides a laminate comprising a base film and a sealant layer, the base film comprising a mechanically recycled polyethylene terephthalate film, and a cyclic trimer content in the mechanically recycled polyethylene terephthalate film being 0.80 mass% or less.
[0006] The laminate contains a mechanically recycled polyethylene terephthalate film (MR-PET film) with a cyclic trimer content of 0.80% by mass or less. Since the cyclic trimer content in the MR-PET film is low, even if pinholes are formed in the laminate, the amount of cyclic trimer penetrating into the laminate is reduced, improving the hygiene of the laminate.
[0007] According to one aspect of the present disclosure, there is provided a packaging bag including the laminate. By including the laminate, the packaging bag has high hygiene.
[0008] One aspect of the present disclosure provides a package including the above-mentioned packaging bag and an item to be contained in a container of the packaging bag. By including the above-mentioned laminate, the above-mentioned packaging bag can reduce the amount of low-molecular-weight compounds such as cyclic trimers that penetrate into the inside of the packaging bag even if a pinhole occurs in the packaging bag, and can sufficiently suppress deterioration of the quality of the item. Therefore, the packaging bag can be particularly suitably used when the item requires high hygiene. Effect of the Invention
[0009] The present disclosure can provide a laminate that uses mechanically recycled PET film and yet has sufficiently high hygiene, as well as a packaging bag and a packaging body that include such a laminate. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 illustrates one embodiment of a cross-section of a laminate. [Diagram 2] FIG. 13 illustrates another embodiment of a cross section of a laminate. [Diagram 3] FIG. 1 is an example of a plan view showing an embodiment of a packaging bag. [Figure 4] FIG. 2 shows differential molecular weight distribution curves obtained by GPC measurement of an MR-PET film and a general PET film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present disclosure will be described. However, the following embodiments are examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. The upper or lower limit of the numerical range specified in this specification may be replaced with any value shown in the examples. In addition, the upper and lower limit values described individually may be arbitrarily combined. Unless otherwise specified, the materials or components exemplified in this specification may be used alone or in combination of two or more types. In the description, the same elements or elements having the same functions are given the same reference numerals, and duplicated descriptions are omitted. In addition, the positional relationships such as up, down, left, and right used in the description are based on the positional relationships shown in the drawings, unless otherwise specified.
[0012] 1 is a diagram showing one embodiment of a cross section of a laminate in the present disclosure. The laminate 100 has a sealant layer 30 on one surface of a base film 10. An adhesive layer S is interposed between the base film 10 and the sealant layer 30.
[0013] The base film 10 is a mechanically recycled polyethylene terephthalate film (MR-PET film). The MR-PET film can be obtained by crushing and cleaning polyethylene terephthalate (PET), further treating it at high temperature and reduced pressure for a certain period of time, removing impurities by melt filtration, returning it to PET resin, and processing it into a film. By using the MR-PET film manufactured through such a recycling process as the base film 10, it is possible to reduce the consumption of plastic resources and the CO2 emissions during PET manufacturing, and obtain an environmentally friendly laminate 100.
[0014] The thickness of the base film 10 may be 9 to 100 μm, 9 to 25 μm, or 12 to 16 μm. The thickness of the base film 10 may be adjusted depending on the application or the desired characteristics. If the thickness is too thick, the sealing performance during packaging may decrease, and the flexibility of the package may decrease, which may cause problems during packaging. If the thickness is too thin, the package may not have sufficient stiffness, and problems such as wrinkles may easily occur during packaging.
[0015] The content of the cyclic trimer contained in the base film 10 is 0.80% by mass or less, and may be 0.70% by mass or less. A laminate 100 including a base film 10 having a cyclic trimer content within the above range can reduce the amount of the cyclic trimer penetrating into the interior even if pinholes are formed, and is sufficiently hygienic. The content of the cyclic trimer may be 0.01% by mass or more.
[0016] The content of the cyclic tetramer contained in the base film 10 may be 0.25% by mass or less. When the content of the cyclic tetramer is within the above range, the amount of cyclic oligomers in the base film 10 can be further reduced. Therefore, the hygiene of the laminate 100 can be further improved. The content of the cyclic tetramer may be 0.01% by mass or more.
[0017] The total content of cyclic pentamers contained in the base film 10 may be 0.09% by mass or less. The total content of cyclic pentamers can be determined by the method described in the Examples. When the content of cyclic pentamers is within the above range, the amount of cyclic oligomers in the base film 10 can be further reduced. Therefore, the hygiene of the laminate 100 can be further improved. The total content of cyclic pentamers may be 0.01% by mass or more.
[0018] The respective contents of the cyclic oligomer trimers, tetramers, and pentamers can be measured, for example, by dissolving the base film 10 in a mixed solvent of hexafluoroisopropanol and chloroform, adding acetonitrile to precipitate the polymer components, and analyzing the supernatant using HPLC (High Performance Liquid Chromatography). The total content of the cyclic oligomer trimers, tetramers, and pentamers may be 1.2% by mass or less, or 1.0% by mass or less. By reducing the total content of the cyclic oligomers, the hygienic properties of the laminate 100 can be further improved. The total content of the cyclic oligomer trimers, tetramers, and pentamers may be 0.80% by mass or more, or 0.90% by mass or more.
[0019] The area ratio of the region with a weight average molecular weight of 1000 or less in a molecular weight distribution curve obtained by GPC (Gel Permeation Chromatography) measurement of the base film 10 may be 4.0% or less of the total peak area, and preferably 3.9% or less. In such a base film 10, the content of low molecular weights inside is sufficiently reduced. Therefore, the hygiene of the laminate 100 can be further improved. The area ratio of the region with a weight average molecular weight of 1000 or less may be 0.1% or more of the total peak area.
[0020] The GPC measurement of the base film 10 can be performed in accordance with JIS K 7252:2008 "Plastics - Determination of average molecular weight and molecular weight distribution of polymers by size exclusion chromatography - Part 1: General rules."
[0021] The base film 10 may be a stretched film or an unstretched film. It is believed that the orientation degree of the crystals in the polymer film is improved by stretching the film. Therefore, it is preferable to use a stretched film from the viewpoint of increasing the oriented crystals in the film and improving the puncture strength. The stretching direction may be the MD direction or the TD direction. In addition, the stretching method may be any method that can provide a film with stable dimensions, such as uniaxial stretching or biaxial stretching. It is preferable to use a biaxially stretched film as the base film 10 from the viewpoint of further improving the puncture strength.
[0022] The sealant layer 30 is a layer that imparts heat-sealing properties to the laminate 100. Examples of components of the sealant layer 30 include thermoplastic resins, specifically, polyolefin resins such as low-density polyethylene (LDPE), medium-density polyethylene (MDPE), linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer (EVA), and ethylene-α-olefin copolymer, ethylene resins such as ethylene-(meth)acrylic acid copolymer, blend resins of polyethylene and polybutene, homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, and polypropylene resins such as propylene-α-olefin copolymer, etc. In addition, the sealant layer 30 may contain one of a plurality of types of these thermoplastic resins alone or in combination.
[0023] The resin constituting the sealant layer 30 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0024] The thickness of the sealant layer 30 is preferably adjusted depending on the mass of the contents, the shape of the packaging bag, etc. The thickness of the sealant layer 30 is preferably, for example, 10 to 100 μm.
[0025] An adhesive layer S is interposed between the base film 10 and the sealant layer 30. Examples of adhesive materials that can be used include polyester-isocyanate resins, urethane resins, and polyether resins. By interposing the adhesive layer S, the base film 10 and the sealant layer 30 can be bonded more firmly.
[0026] The thickness of the adhesive layer S is not particularly limited and may be, for example, 0.5 to 5 μm or 2 to 3 μm. When the thickness of the adhesive layer S is 0.5 μm or more, the adhesion between the base film 10 and the sealant layer 30 can be improved, and when it is 5 μm or less, the laminate 100 can be easily recycled.
[0027] Examples of methods for forming the laminate 100 include a dry lamination method in which a film-like sealant layer 30 made of the above-mentioned thermoplastic resin is laminated onto the base film 10 using an adhesive such as a one-component curing or two-component curing urethane adhesive, a non-solvent dry lamination method in which a film-like sealant layer 30 is laminated onto the base film 10 using a solvent-free adhesive, and an extrusion lamination method in which the above-mentioned thermoplastic resin is heated and melted, extruded into a curtain shape, and laminated. The adhesive used to laminate the sealant layer 30 onto the base film 10 forms an adhesive layer S as shown in FIG. 1. The sealant layer 30 may be directly laminated onto the base film 10 without the adhesive layer S.
[0028] A printing layer can be provided on the surface of the base film 10 on the side of the sealant layer 30. The printing layer is provided at a position visible from the outside of the laminate for the purpose of displaying information about the contents, identifying the contents, or improving the design of the packaging bag. The printing method and printing ink are not particularly limited, and are appropriately selected from known printing methods and printing inks in consideration of printability on the film, design such as color tone, adhesion, safety as a food container, and the like. Examples of printing methods that can be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Of these printing methods, gravure printing is preferred from the viewpoints of productivity and high definition of the image.
[0029] In order to improve the adhesion of the printed layer, the surface of the base film 10 on the printed layer side may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.
[0030] Fig. 2 is a diagram showing another embodiment of a cross section of a laminate in the present disclosure. As shown in Fig. 2, the laminate 101 includes an intermediate layer 20 between the base film 10 and the sealant layer 30. The configuration of the intermediate layer 20 can be appropriately referred to the contents described above regarding the configuration of the sealant layer 30. By including the intermediate layer 20 in the laminate 101, deformation of the laminate during the manufacture of a packaging bag can be further reduced. A plurality of intermediate layers 20 may be used depending on the application of the laminate 101.
[0031] As shown in Fig. 2, a metal layer 40 may be laminated between the intermediate layer 20 and the sealant layer 30. The metal layer 40 may be laminated between the base film 10 and the intermediate layer 20, taking into consideration the manufacturing conditions. By providing the laminate 101 with the metal layer 40, the puncture strength and gas barrier properties of the laminate can be improved. In addition, the metal layer 40 may be vapor-deposited on the intermediate layer 20 in advance.
[0032] An anchor coat layer may be provided adjacent to at least one selected from the printed layer and the metal layer 40. By providing the anchor coat layer, the adhesion of the printed layer or the metal layer 40 can be increased, and the puncture strength of the laminate 100, 101 can be further improved. The anchor coat layer can be formed by applying an anchor coat agent onto a predetermined layer and drying it. For example, polyester-based polyurethane resin, polyether-based polyurethane resin, etc. can be used as the anchor coat agent. The thickness of the anchor coat layer is not particularly limited, but may be 0.1 to 1 μm, or 0.3 to 0.5 μm.
[0033] As the metal layer 40, a known metal foil such as copper foil or aluminum foil can be used. From the viewpoint of improving the gas barrier property or preventing the transmission of visible light and ultraviolet light, it is preferable to use aluminum foil. The thickness of the metal layer 40 may be, for example, 6 to 9 μm. By making the thickness of the metal layer 40 6 μm or more, the piercing strength of the laminate 101 is improved. Therefore, even if a foreign matter adheres to the base film 10 in a package including the laminate 101, the problem of the foreign matter penetrating inside the base film 10 can be prevented. Furthermore, it is possible to prevent low molecules such as cyclic oligomers contained in the base film 10 from penetrating inside the base film 10. Therefore, deterioration of the quality of the contents can be suppressed.
[0034] By performing X-ray diffraction measurement on the surface x (surface of the substrate film 10) on the substrate film 10 side of the laminate 100, 101, a peak pattern showing the crystalline state of the MR-PET film can be obtained. When the peak intensity value of the halo peak (diffraction line originating from amorphous material) detected at 2θ of 20° among the peaks obtained by X-ray diffraction measurement is I0 and the peak intensity value of the (100) plane of PET is I1, I1 / I0 may be 18 or more, or may be 19 or more. For example, the measurement can be performed using an X-ray diffraction device (RINT ULTIMA III, manufactured by Rigaku Corporation) with an X-ray source of Cu-Kα radiation, a diffraction angle of 10°<2θ<40°, a voltage of 40 kV, and an output of 40 mA current. The peak intensity value indicates the height (cps) of the peak based on the baseline.
[0035] Pre-processing such as smoothing of the peak pattern obtained by X-ray diffraction measurement and background processing may be performed by a known method that is installed as standard in the X-ray diffraction device. Examples of methods for background processing of the peak pattern include the manual (spline) method and the SONNVELT-VISSEER method. In the present disclosure, the manual (spline) method is used from the viewpoint of reducing the variation in peak intensity after background processing and improving accuracy. The manual (spline) method is a method in which two 2θ positions are specified, and a spline approximation line passing through the two points is used as the background. The minimum value of the 2θ position may be 5 to 15°. The maximum value of the 2θ position may be 35 to 45°.
[0036] X-ray diffraction measurements reveal a broad halo peak at 2θ of around 20°, which is usually due to amorphous matter. The presence of such a halo peak confirms the presence of amorphous matter in the MR-PET film. By specifying the 2θ at which the halo peak is detected as 20°, the variation in the peak intensity value (I0) of the halo peak can be suppressed.
[0037] X-ray diffraction measurements show a peak at 2θ of around 26° that is attributable to the (100) plane of MR-PET. The presence of such a peak attributable to the (100) plane of MR-PET confirms that there is a high proportion of crystals oriented in a specific direction in the MR-PET. The (100) plane was chosen because this is usually the largest peak in stretched MR-PET films.
[0038] Among the peaks obtained by X-ray diffraction, the method of specifying the halo peak (2θ=20°) with a peak intensity value of I0 is performed manually using the analysis software attached to the X-ray diffraction device, but the peak of the PET (100) plane with a peak intensity value of I1 is the peak automatically detected by peak search processing using the analysis software attached to the X-ray diffraction device.
[0039] When the peak intensity value of the above-mentioned halo peak is I0 and the peak intensity value derived from the (100) plane of MR-PET is I1, I1 / I0 may be 18 or more. The obtained I1 / I0 represents the ratio of oriented crystals to amorphous matter, and can be regarded as the crystallinity index of MR-PET. Therefore, the laminates 100 and 101 having a crystallinity index of 18 or more have high puncture strength due to the low ratio of amorphous matter and the high ratio of oriented crystal matter in the MR-PET film.
[0040] The crystallinity index may be 19 or more. When the crystallinity index is in this range, a laminate including an MR-PET film having a lower amorphous content and a higher oriented crystalline content can be obtained. Therefore, such a laminate has a higher puncture strength.
[0041] The puncture strength of the laminates 100, 101 can be measured based on "7.5 Puncture Strength Test" of JIS Z1707:2019 "General Rules for Food Packaging Plastic Films". For example, the measurement can be performed by piercing the laminates 100, 101 from the surface x on the base film 10 side toward the opposite side using a Tensilon AD-7303 (manufactured by A&D Co., Ltd.). The puncture strength of the laminates 100, 101 may be 8.6 N or more, or may be 8.7 N or more. By providing a laminate having such a puncture strength, a packaging bag and a packaging body having high puncture strength can be obtained. Therefore, a packaging body having high hygienic properties, in which low molecules such as cyclic oligomers are less likely to penetrate inside, can be obtained. The puncture strength of the laminates 100, 101 may be 10.0 N or less.
[0042] The puncture strength of the base film 10 may be 7.7 N or more, or may be 7.8 N or more. This can improve the puncture strength of the laminates 100, 101, and provide laminates with even higher hygiene. The puncture strength of the base film 10 may be 9.0 N or less.
[0043] The laminates 100, 101 may include, as the base film 10, the MR-PET film having the I1 / I0 of 38 or more when the MR-PET film alone is subjected to X-ray diffraction measurement. The method for measuring the X-ray diffraction and puncture strength is as described above. By using an MR-PET film having an I1 / I0 of 38 or more as the base film 10, the laminates 100, 101 having even higher puncture strength can be obtained. In this case, from the viewpoint of further increasing the puncture strength of the laminate, the I1 / I0 may be 39 or more, or may be 40 or more. The I1 / I0 of the MR-PET film alone may be 50 or less.
[0044] 3 is an example of a plan view showing one embodiment of a packaging bag formed using a laminate. The packaging bag 200 includes a sealed portion 211 formed by bonding the peripheries of a pair of substantially rectangular laminates 100 together, and a storage portion 218 formed between the pair of laminates 100, 100 by the sealed portion 211. That is, the packaging bag 200 has a side end portion 214, a lower end portion 216, and an upper end portion 217 sealed by the sealed portion 211. The packaging bag 200 includes a storage portion 218 in which an object such as food is stored, in a non-sealed portion 215 surrounded by the sealed portion 211. The object such as food is enclosed in the storage portion 218. The sealed portion 211 at the lower end portion 216 may be sealed after the object is filled in the storage portion 218.
[0045] The pair of laminates 100 are overlapped with the sealant layers 30 facing each other. The pair of laminates 100 may be bonded to each other at the seal portion 211 by an adhesive. The pair of laminates 100 may form the seal portion 211 by bonding the heat seal layers provided on the sealant layers 30 to each other.
[0046] The laminate 100 has a high puncture strength, and therefore can sufficiently prevent pinholes from occurring. In addition, the content of cyclic trimers in the base film 10 is low, and therefore the laminate 100 is hygienic. This can sufficiently prevent low molecular weight components such as cyclic oligomers, trace components, PET components, or outside air from entering the inside of the packaging bag 200 through pinholes, and can sufficiently prevent contamination or deterioration of the contents contained in the storage section 218. The packaging bag 200 may have any layer on the base film 10 and the sealant layer 30 of the laminate 100.
[0047] The procedure for manufacturing a packaging bag 200 (packaging body) using the laminate 100 is described below. A pair of laminates 100 is prepared. In the case of the laminate 100, the sealant layers 30 of the laminates 100 are placed opposite each other, and the sealant layers 30 are bonded together with, for example, a fastener tape interposed therebetween, which serves as the resealing means 230. This forms sealed portions 211 at positions corresponding to the upper end 217 and the side ends 214, 214, and forms a non-sealed portion 215 surrounded by the sealed portions 211 in a U-shape.
[0048] After the sealing portion 211 is formed, the opening means 220 may be formed. For example, the side end portions 214, 214 are formed with easy-to-open processed portions 224, 224 consisting of a group of scars. The easy-to-open processed portions 224 are not limited to a group of scars, and may be V-shaped, U-shaped, I-shaped or other notches. In addition, a half-cut line 221 that serves as a trajectory for cutting from the easy-to-open processed portion 224 may be formed on the surface portion of the laminate 100 between the upper end portion 217 and the resealing means 230. The half-cut line 221 can be formed using a laser beam. After the opening means 220 is formed, the sealing portion 211 is cut and trimmed to separate the package into individual packaging bags.
[0049] Next, the contents are filled from the unsealed lower end 216. Thereafter, the laminates 100 are bonded together at the lower end 216, and a seal portion 211 is also formed at the lower end 216. In this manner, the packaging bag 200 and the package can be manufactured. The half-cut line may be formed before the pair of laminates 100 that have been bonded together are slit to a predetermined width.
[0050] The packaging bag 200 is provided with opening means 220 at the upper end side of the non-sealed portion 215 for cutting open the side ends 214, 214 of the packaging bag 200 and across the space therebetween to open the bag, and resealing means 230 below the opening means 220 for resealing the storage portion 218 after the bag is opened by the opening means 220. The resealing means 230 may appropriately adopt a known structure capable of repeatedly opening and sealing. For example, the resealing means 230 may be a synthetic resin fastener capable of repeatedly sealing by fitting a strip-shaped protrusion into a strip-shaped groove, or may be an adhesive seal.
[0051] The package includes a packaging bag 200 and an object contained in the container 218 of the packaging bag 200. Examples of the object include food, electronic materials, and electronic devices. The package includes the packaging bag 200, and therefore the content of cyclic trimers is low, and it is possible to prevent the object from being altered or deteriorated due to the intrusion of low molecular weight components such as cyclic oligomers, trace components, PET components, or outside air through pinholes generated by piercing. In addition, since recycled PET can be used as the packaging bag, it is possible to provide an environmentally friendly and highly hygienic package.
[0052] Although several embodiments of the present disclosure have been described above, the present disclosure is not limited to the above embodiments. For example, the laminate 100 and the laminate 101 used in the above description may be appropriately replaced with each other. The laminates 100 and 101 may have any layer or thin film between the base film 10 and the sealant layer 30, between the base film 10 and the intermediate layer 20, or between the intermediate layer 20 and the sealant layer 30, as long as the function of the laminate is not significantly impaired. The shape of the packaging bag 200 and the packaging body is not limited to a four-sided bag. For example, it may be a two-sided bag, a three-sided bag, or a palm-shaped bag, or it may be a standing pouch shape with a bottom tape added.
[0053] The present disclosure includes the following embodiments. [1] A laminate comprising a base film and a sealant layer, The base film includes a mechanically recycled polyethylene terephthalate film, A laminate, wherein the mechanically recycled polyethylene terephthalate film has a cyclic trimer content of 0.80 mass% or less. [2] The laminate according to [1], wherein the area ratio of the region having a weight average molecular weight of 1000 or less in a molecular weight distribution curve obtained by GPC measurement of the mechanically recycled polyethylene terephthalate film is 4.0% or less of the total peak area. [3] The laminate according to [1] or [2], wherein the mechanically recycled polyethylene terephthalate film has a cyclic tetramer content of 0.25 mass% or less. [4] The laminate according to any one of [1] to [3], which has a puncture strength of 8.6 N or more. [5] The laminate according to any one of [1] to [4], wherein the surface of the laminate on the base film side is measured by X-ray diffraction, and when the peak intensity value detected when 2θ is 20° is I0 and the peak intensity value of the (100) plane of polyethylene terephthalate is I1, I1 / I0 is 18 or more. [6] The laminate according to any one of the above [1] to [5], comprising as the base film the mechanically recycled polyethylene terephthalate film, in which the surface of the mechanically recycled polyethylene terephthalate film alone is measured by X-ray diffraction, and the I1 / I0 is 38 or more, where I0 is the peak intensity value detected when 2θ is 20°, and I1 is the peak intensity value of the (100) plane of the polyethylene terephthalate. [7] The laminate according to any one of [1] to [6], wherein the mechanically recycled polyethylene terephthalate film has a thickness of 9 to 100 μm. [8] A packaging bag comprising the laminate according to any one of the above [1] to [7]. [9] A packaging body comprising the packaging bag described in [8] above and an item contained in the storage section of the packaging bag. EXAMPLES
[0054] The present disclosure will be described in more detail below with reference to examples, comparative examples, and reference examples. Note that the present disclosure is not limited to the following examples.
[0055] [Gel Permeation Chromatography (GPC) measurement of polyethylene terephthalate (PET) film] A commercially available mechanically recycled PET film (MR-PET film) and a commercially available PET film (general PET film) that had not been recycled were prepared. Hereinafter, the term "PET film" refers to both MR-PET film and general film. The thickness of each PET film was 12 μm.
[0056] Each PET film was dissolved in hexafluoroisopropanol containing 5 mM sodium trifluoroacetate to a concentration of 0.1 w / v%, and filtered through a filter with a pore size of 0.45 μm to prepare a measurement sample. The polymethyl methacrylate-equivalent molecular weight of each PET film was measured under the following conditions in accordance with JIS K 7252:2008 "Plastics - Determination of average molecular weight and molecular weight distribution of polymers by size exclusion chromatography - Part 1: General rules".
[0057] Column: Shodex GPC LF-404 (manufactured by Resonac Co., Ltd.) Oven temperature: 40℃ Eluent: 5 mM sodium trifluoroacetate in hexafluoroisopropanol ·Flow rate: 0.15mL / min Detector: RI Standard sample: Polymethyl methacrylate ·Injection volume: 20μL
[0058] As a result of GPC measurement, the weight average molecular weight of the MR-PET film was 12500 and the number average molecular weight was 4600. On the other hand, the weight average molecular weight of the general PET film was 12700 and the number average molecular weight was 4600. In addition, the ratio of the peak area of the weight average molecular weight of 1000 or less to the total peak area of the weight average molecular weight was 3.8% for both the MR-PET film and the general PET film, as shown in Table 1. The differential molecular weight distribution curves for each PET film are shown in Figure 4. The solid line A in Figure 4 shows the differential molecular weight distribution curve of the MR-PET film, and the dashed line B shows the differential molecular weight distribution curve of the general PET film. The horizontal axis of Figure 4 shows the logarithm of the weight average molecular weight, and the vertical axis of Figure 4 shows the differential value of the logarithm of the weight average molecular weight.
[0059] [Measurement of cyclic oligomer content in PET film] 50 mg of PET film was dissolved in 1 mL of hexafluoroisopropanol, and then 2 mL of chloroform was added, followed by the addition of acetonitrile to precipitate the polymer. The resulting supernatant was adjusted to 50 mL with acetonitrile and subjected to HPLC (High Performance Liquid Chromatography). Dimethyl terephthalate was used as the standard substance to measure the contents of cyclic trimer, cyclic tetramer, and cyclic pentamer. The HPLC measurement was performed under the following conditions.
[0060] Measurement equipment: 1200 Series (manufactured by Agilent Technology, Inc.) Column: L-column ODS (manufactured by Chemicals Evaluation and Research Institute, Japan) Length: 250mm, inner diameter: 4.6mm, particle size: 5μm Column temperature: 40℃ Mobile phase: acetonitrile / water = 7 / 3 (volume ratio) ·Flow rate: 1.5mL / min ·Injection volume: 20μL Detector: Photodiode array detector ·Measurement wavelength: 242nm
[0061] Among the peaks obtained by HPLC measurement, the peak detected at a retention time of 5.9 minutes was taken as the cyclic trimer, and the peak detected at 10.0 minutes was taken as the cyclic tetramer, and the content was calculated from the peak area of each. In addition, the peaks detected at retention times of 11.9 minutes and 15.1 minutes were taken as the cyclic pentamer, and the content was calculated from the peak area of each. In addition, the total content of the cyclic pentamer was calculated from the sum of the calculated contents. The total content of the cyclic oligomer was calculated from the total content of the cyclic trimer, cyclic tetramer, and cyclic pentamer. The results are shown in Table 1.
[0062] [X-ray diffraction measurement of PET film] Each PET film was cut into three pieces of 4.8 cm x 4.8 cm sample pieces. The PET film sample pieces were designated n1, n2, and n3, respectively. The obtained sample pieces were measured under the following conditions using a RINT ULTIMA III (manufactured by Rigaku Corporation). Since it was confirmed that there were no diffraction lines originating from the sample due to Cu-Kβ rays, a Ni filter was not used to prevent a decrease in the intensity of the diffraction lines originating from the sample due to Cu-Kα rays.
[0063] ·X-ray source: Cu-Kα Voltage: 40kV ·Current: 40mA Scan method: 2θ-θ method (parallel beam method) Counting unit: cps Scanning speed: 4° / min Measurement range: 10°<2θ<40° Sampling speed: 0.020° / min -Sample stage control mode: Rotation Ni filter: Not used
[0064] For the peak pattern of each PET film, the smoothing process was performed at 19 points, and two points, 2θ=10° and 2θ=40°, were selected, and background processing was performed between the two points by manual (spline) method. From the peak pattern after processing, the peak intensity value when 2θ is 20° was defined as I0, and the peak intensity value originating from the (100) plane of PET occurring at 2θ around 26° was defined as I1, and the crystallinity index of each sample piece, expressed as I1 / I0, was calculated. The results are shown in Table 1.
[0065] [PET film puncture strength measurement] The puncture strength of the sample pieces subjected to the above X-ray measurement was measured based on "7.5 Puncture Strength Test" of JIS Z1707:2019 "General Rules for Food Packaging Plastic Films". The measuring device used was Tensilon AD-7703 (manufactured by A&D Co., Ltd.). The results are shown in Table 1.
[0066] Test speed: 50mm / min Load cell: 100N Load range: 10N (10%)
[0067] [Laminated body production] Example 1 A laminate was produced using an MR-PET film as the base film in the following procedure. A printed layer was formed on one side of the base film. An anchor coating agent containing a polyester-based polyurethane resin was applied to the printed layer to form a first anchor coating layer (AC1) with a thickness of 0.5 μm.
[0068] A polyethylene film (PE1, thickness: 15 μm) was attached onto the first anchor coat layer by extrusion lamination, and aluminum foil (thickness: 7 μm) was vapor-deposited onto the polyethylene film. An anchor coating agent was applied onto the vapor-deposited aluminum foil to form a second anchor coat layer (AC2) with a thickness of 0.5 μm.
[0069] A polyethylene film (PE2, thickness: 25 μm) was bonded as a sealant layer onto the prepared second anchor coat layer by extrusion lamination. In this way, a laminate was prepared. The prepared laminate was cut into three sample pieces of 4.8 cm × 4.8 cm. The obtained sample pieces were designated n1, n2, and n3, respectively.
[0070] The layer structure of the laminate of this example is as follows. PE2 / adhesive layer / AC2 / aluminum foil / PE1 / adhesive layer / AC1 / printing layer / MR-PET
[0071] Comparative Example 1 A laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that a general PET film was used as the base film instead of the MR-PET film. The produced laminate was cut into three sample pieces of 4.8 cm x 4.8 cm. The obtained sample pieces were designated n1, n2, and n3, respectively.
[0072] The layer structure of the laminate of this comparative example is as follows. PE2 / adhesive layer / AC2 / aluminum foil / PE1 / adhesive layer / AC1 / printing layer / general PET
[0073] [Measurement of crystallinity index and puncture strength of laminate] X-ray diffraction measurements were performed on the surface of the substrate film side of each sample piece of Example 1 and Comparative Example 1, and the crystallinity index was calculated. The conditions for the X-ray measurements were as described above. Furthermore, the surface of the substrate film side of each sample piece subjected to the X-ray measurements was measured for puncture strength. The method for measuring the puncture strength was as described above, except that the load range was set to 20N (20%). The measurement results are shown in Table 1.
[0074] [Table 1]
[0075] As shown in Table 1 and Figure 4, there was no significant difference in the distribution of weight-average molecular weight by GPC between the MR-PET film and the general PET film, nor was there a significant difference in the proportion of low molecular weight molecules with a weight-average molecular weight of 1000 or less. On the other hand, the MR-PET film had a lower content of cyclic trimers, cyclic tetramers, and cyclic pentamers than the general PET film. Therefore, it was confirmed that the laminate using the MR-PET film has a low content of cyclic oligomers and is highly hygienic.
[0076] The puncture strength of the PET film was lower for the MR-PET film than for the general PET film. However, when laminated, the laminate using the MR-PET film as the base film had a higher puncture strength than the laminate using the general PET film as the base film. The crystallinity index of the laminate using the MR-PET film was also higher than that of the laminate using the general PET film. Therefore, it was confirmed that a packaging bag having high puncture strength can be obtained by using a laminate using the MR-PET film as the base film for a packaging bag. Furthermore, such a laminate and packaging bag have high puncture strength, and since the content of cyclic oligomers is low, even if a pinhole occurs in the packaging bag, the cyclic oligomer is unlikely to penetrate inside. Therefore, it was confirmed that packaging bags and packaging bodies having sufficiently high hygienic properties can be produced using environmentally friendly mechanically recycled PET film. [Industrial Applicability]
[0077] According to the present disclosure, it is possible to provide a laminate that uses mechanically recycled PET film and yet has sufficiently high hygiene, as well as a packaging bag and a packaging body that include such a laminate. [Explanation of symbols]
[0078] 10...base film, 20...intermediate layer, 30...sealant layer, 40...metal layer, 100, 101...laminate, S...adhesive layer, x...surface, 200...packaging bag, 211...sealed portion, 214...side edge, 215...unsealed portion, 216...lower end, 217...upper end, 218...container portion, 220...opening means, 221...half-cut line, 224...easy-to-open portion, 230...resealing means, A...differential molecular weight distribution curve of MR-PET film, B...differential molecular weight distribution curve of general PET film.
Claims
1. A laminate comprising a base film and a sealant layer, The base film includes a mechanically recycled polyethylene terephthalate film, A laminate, wherein the mechanically recycled polyethylene terephthalate film has a cyclic trimer content of 0.80 mass% or less.
2. The laminate according to claim 1, wherein the area ratio of the region having a weight average molecular weight of 1000 or less in a molecular weight distribution curve obtained by GPC measurement of the mechanically recycled polyethylene terephthalate film is 4.0% or less of the total peak area.
3. The laminate according to claim 1 or 2, wherein the mechanically recycled polyethylene terephthalate film has a cyclic tetramer content of 0.25 mass% or less.
4. The laminate according to claim 1 or 2, which has a puncture strength of 8.6 N or more.
5. The surface of the laminate on the side of the base film is measured by X-ray diffraction, and the peak intensity value detected when 2θ is 20° is defined as I 0 , the peak intensity value of the (100) plane of polyethylene terephthalate is I 1 Then, I 1 / I 0 The laminate according to claim 1 or 2, wherein the number of saturation points is 18 or more.
6. The surface of the mechanically recycled polyethylene terephthalate film was measured by X-ray diffraction, and the peak intensity value detected when 2θ was 20° was defined as I 0 , the peak intensity value of the (100) plane of polyethylene terephthalate is I 1 Then, I 1 / I 0 The laminate according to claim 1 or 2, comprising the mechanically recycled polyethylene terephthalate film having a modulus of elasticity of 38 or more as the base film.
7. The laminate according to claim 1 or 2, wherein the mechanically recycled polyethylene terephthalate film has a thickness of 9 to 100 μm.
8. A packaging bag comprising the laminate according to claim 1 or 2.
9. A package comprising the packaging bag according to claim 8 and an item contained in the container of the packaging bag.
Citation Information
Patent Citations
Printing resin film, laminate having printing resin film and packaging container having laminate, and laminate having polyester film and packaging container having laminate
JP2022002890A